Identitas Islam Moderat dalam Kebijakan Luar Negeri Indonesia - Andriasanti, Lelly (UI Scholars Hub, 2014)
In recent years, Indonesia’s foreign policy seems to portray moderate Islamic identity. This is, however, in contrast with the practices of Indonesia’s foreign policy itself. Historically, Indonesia has been avoiding the possibility of reflecting the Islamic identity, although the majority of Indonesia’s population is Muslim. This situation raises a question, “Why does Indonesia’s current foreign policy promote moderate Islamic identity?” The methodology used in this study is a qualitative method, specifically discourse analysis. There are four results of this study. First of all, by portraying moderate Islamic identity, Indonesia wants to distinguish itself from the other Muslim-majority countries, especially those in the Middle East region. Second, there are expectations from the international community, especially Western countries, to understand and to get closer to the Muslim world. Third, Indonesian Government wants to accommodate the voice of domestic Muslim community that has been expecting a better relation with the Muslim world. Last but not least, in accordance with the consistency of its worldview, Indonesia has a motivation to take part in international relations.